Synthesis of C-N-S-Tridoped TiO2 from Vietnam Ilmenite Ore and Its Visible Light-Driven-Photocatalytic Activity for Tetracyline Degradation - Nguyen Thi Lan; Vo Hoang Anh; Hoang Duc An; Nguyen Phi Hung; Dao Ngoc Nhiem; Bui Van Thang; Pham Khac Lieu; Dinh Quang Khieu (My University, 2020)
Synthesis of C-N-S-Tridoped TiO2 from Vietnam Ilmenite Ore and Its Visible Light-Driven-Photocatalytic Activity for Tetracyline Degradation
Keywords: C-N-S-Tridoped TiO2; Tetracyline; Ilmenite Ore